2023
DOI: 10.1021/acschembio.2c00720
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic ERRα/β/γ Agonist Induces an ERRα-Dependent Acute Aerobic Exercise Response and Enhances Exercise Capacity

Abstract: Repetitive physical exercise induces physiological adaptations in skeletal muscle that improves exercise performance and is effective for the prevention and treatment of several diseases. Genetic evidence indicates that the orphan nuclear receptors estrogen receptor-related receptors (ERRs) play an important role in skeletal muscle exercise capacity. Three ERR subtypes exist (ERRα, β, and γ), and although ERRβ/γ agonists have been designed, there have been significant difficulties in designing compounds with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Given that ERRα and ERRγ share many common target genes, 11 it is somewhat surprising that ERRγ is responsible for most of the 332-or 915-induced metabolic gene transcription. 21 Previous studies showed that all ERR isoforms exhibit a basal level of transcriptional activity independent of ligand binding. [109][110][111][112][113][114] ERR isoforms may have different levels of basal activity resulting in differentially inducible activity by ERR agonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that ERRα and ERRγ share many common target genes, 11 it is somewhat surprising that ERRγ is responsible for most of the 332-or 915-induced metabolic gene transcription. 21 Previous studies showed that all ERR isoforms exhibit a basal level of transcriptional activity independent of ligand binding. [109][110][111][112][113][114] ERR isoforms may have different levels of basal activity resulting in differentially inducible activity by ERR agonists.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we report the cardioprotective effect of a recently described pan-ERR agonist SLU-PP-332 (332) 21 and another structurally distinct pan-ERR agonist SLU-PP-915 (915) in pressure overload-induced HF. Our data show that 332/915, mainly through ERRγ, activated a broad spectrum of metabolic genes, enhanced fatty acid metabolism and mitochondrial function, and improved contractile function in transaortic constriction (TAC)-induced HF in vivo.…”
mentioning
confidence: 99%
“…Collectively, our study demonstrates an essential role of the ERRα phosphorylation state in the control of muscle functions and energy metabolism during endurance exercise, highlighting ERRα hyperactivation as a potential therapeutic target to improve exercise performance and achieve long-term exercise benefits [ 73 ]. Future work will help delineate the exact contribution of post-translational mechanisms contributing to exercise-induced ERRα stabilization and overall activity.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intake of γ-Oryzanol, a mixture of ferulic acid esters of terpenoids similar to ABA, used as a sports supplement, was shown to improve muscle strength and exercise endurance in mice by upregulating the transcription of both ERRα/γ via PPARδ [84]. In another study, a synthetic pan-ERR agonist was shown to induce a transcriptional reprogramming of type IIA muscle fibers as observed in aerobic training and to increase physical endurance in mice [85]. Finally, a recently published study describes how the expression of a mutated form of ERRα, resistant to phosphorylation-induced inactivation, induces muscle fiber aerobic transformation and increases mitochondrial biogenesis, metabolic fuel oxidation, and physical endurance in mice [86].…”
Section: Skeletal Musclementioning
confidence: 97%